Perspective of fathers and their daughters on her heterosexual relationship - Dos Santos, Stephanie Denise E.; Saamong, Charla Rochella S. (Quezon City College of Home Economics, University of the Philippines, Diliman, 2016)
This research presents the similarities and differences in the contemporary perspective of the Filipino fathers and daughters on her first heterosexual relationship. Furthermore, this research provides studies and discussions on the relationship shared between fathers and daughters and the lasting impact it brings unto the daughters as they mature. Fifteen Filipino father and daughter dyads participated in a semi-structured interview to identify their perspectives when it comes to the daughter's heterosexual relationships. Fathers'and daughters' responses on their description and knowledge of the heterosexual relationship, conflicts and disagreements they encounter with each other, established rules, guidelines, and consequent feelings were equally taken into account. Findings show that majority of the daughters agree with their fathers who did not set an age or life circumstances on when they can engage in heterosexual relationships. Moreover, a large number of fathers and daughters describe their relationship with each other to be open and void conflicts and disagreements. Finally, most daughters agree with their fathers' approach on the setting rules and guidelines for them and see that their fathers' perspective have a positive influence on their heterosexual relationships.
Thesis (BS in Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Fathers and daughters -- Philippines